PENGARUH CORPORATE MARKETING PERFORMANCE TERHADAP NILAI PERUSAHAAN : BUKTI DARI PASAR NEGARA ASEAN - Rohwiyati; Sulistya; Marhaendra Kusuma; Nashya Youllanda; Sanju Kumar Singh (STIE PGRI Dewantara Jombang, 2026)
This research investigates the effect of corporate marketing performance on firm value and the moderating role of unrealized income in the influence of corporate marketing performance on firm value. Data are drawn from the financial statements of financial sector companies listed on the capital markets in five ASEAN member countries for the years 2020-2024, with a sample of 207 entities and observational data from 1,035 firm-years. Hypothesis testing uses moderated regression analysis. The results of the investigation indicate that corporate marketing performance has a positive effect on firm value, supporting classical marketing theory. Unrealized income strengthens the influence of corporate marketing performance on firm value, supporting signaling theory. The originality of this study lies in examining the moderating role of unrealized income in the influence of corporate marketing performance on firm value.